Performance evaluation of Moringa oleifera seeds aqueous extract for removing Microcystis aeruginosa and microcystins from municipal treated-water - Alhaithloul, Haifa A. S.; Mohamed, Zakaria A.; Saber, Abdullah A.; Alsudays, Ibtisam Mohammed; Abdein, Mohamed A.; Alqahtani, Mesfer M.; AbuSetta, Noha G.; Elkelish, Amr; Pérez, Leonardo Martín; Albalwe, Fauzeya Mateq; Bakr, Asmaa A. (Frontiers in Bioengineering and Biotechnology, 2024)
Toxic microcystins (MCs) produced by cyanoprokaryotes, particularly by the cosmopolitan cyanobacterium Microcystis aeruginosa, pose adverse effects on aquatic organisms and their ecosystem, and may also have a serious impact on human health. These harmful monocyclic heptapeptides are the most prevalent cyanotoxins reported in freshwaters and have to be eliminated prior to release in the receiving water bodies. Hence, this work aimed to test the efficacy of Moringa oleifera seeds water-based extract as a natural coagulant for removing cyanobacteria and microalgae, especially M. aeruginosa and associated MCs, from pre-treated municipal waters. For this, four different coagulant doses (25, 50, 75 and 100 mg L -1 ) were investigated for algae removal using conventional coagulation assays and morphology-based taxonomy. Our findings showed that treatment with M. oleifera seeds aqueous extract at 100 mg L -1 substantially reduced the number of cyanobacterial and microalgal species in the treated samples (average removal rate of 93.8% and 86.9, respectively). These results agreed with a ~44% concomitant reduction in chlorophyll a (Chl a) and ~97% reduction in water turbidity (a surrogate marker for suspended solids content). Further, the presence and concentration of MCs soluble in water, remaining in the particulate fraction, and flocculated within the residual sludge were assessed using high-performance liquid chromatography (HPLC-DAD). Notably, MCs concentrations in treated water were significantly lowered, particularly the treatment with M. oleifera seeds aqueous extract at 100 mg L -1 (0.6 ± 0.1 µg L -1 MCs), to levels below the WHO recommended limits for drinking water (<1.0 µg L -1 ). Possible mechanisms of action were also discussed.As a consequence, the present study provides promising insights into the applicability of M. oleifera seeds aqueous extracts as a cost-effective, reliable, and sustainable natural coagulant, particularly for the developing countries, to eliminate harmful cyanobacteria and cyanotoxins in municipal water treatment facilities.